A Stable, Low Permeable TEMPO Catholyte for Aqueous Total Organic Redox Flow Batteries (Adv. Energy Mater. 8/2022). Issue 8 (24th February 2022) - Hu, Bo; Hu, Maowei; Luo, Jian; Liu, T. Leo
Abstract : Redox Flow Batteries In article number 2102577, T. Leo Liu and co‐workers report a dual ammonium functionalized TEMPO molecule as a stable, low permeable organic catholyte for aqueous organic redox flow batteries. The presented molecular design strategy is expected to aid the development of advanced redox active organic electrolytes for sustainable, long‐duration energy storage.